Determinants of Unsuccessful Prehospital Resuscitation in Pediatric Emergencies - Mousaeinejad, Negin; Khosravi, Shaqayeq; Jafarnejad, Shabahang; Mahyapour Lori, Zahra; Khosravi, Kiana; Aghajani Delavar, Motahare; Marashi, Sayed Mahdi; Nasri-Nasrabadi, Zeynab (International Journal of Medical Toxicology and Forensic Medicine, 2026)
Background: Children are especially vulnerable to potentially fatal injuries from illness or accidents. This study aims to examine the circumstances surrounding out-of-hospital cardiac arrest and to evaluate unsuccessful emergency rescue attempts. Methods: This retrospective study reviewed records of patients under 18 years admitted to Iran University of Medical Sciences–affiliated hospitals from March 2013 to March 2024. The study included children who received emergency medical services and were transported during ongoing CPR. Results: Among 134 cases, the mean age was 4.75 years and male-to-female ratio was 1.39:1. While 61.9% were Iranian, 38.1% were Afghans. Mortality was highest in infants under one year (35.1%) and in children aged 1–5 years (25.4%). The leading causes of death were underlying medical illnesses, followed by accidents, notably pedestrian collisions. Conclusion: Cardiac arrest due to medical illnesses at home and pedestrian accidents account for a large share of unsuccessful pre-hospital resuscitations, most of which are preventable. Migrant children have a markedly higher mortality risk, likely due to socio-economic factors. These findings call for targeted injury prevention and policy reforms to address migrant populations and reduce the public health burden.